Evaluación del uso eficiente del agua en el cultivo de maíz (Zea mays) variedad INIAP 101, bajo diferentes niveles de fertilización - Velásquez Iturralde, Ricardo Daniel (2022)
Corn cultivation is one of the most important cereals in the world, because it provides food for humans and animals and has become a fundamental ingredient in the starch, flour, oil and protein processing industry, in the production of alcoholic beverages, food sweeteners and recently, fuel. In Ecuador, in the Sierra Region, it is one of the most important crops, this is due to the large amount of land used for its production and the role it plays as a basic component in the population's diet. However, there are problems in the use of an irrigation system and adequate fertilization, which makes it an opportunity for technological improvement in the crop. The objective of the research is to evaluate the efficient use of water in the cultivation of soft corn, variety INIAP 101, with different levels of fertilization to contribute to the development and increase of production, by obtaining a product of better quality and performance. The experiment was carried out at the National Institute of Agricultural Research, Santa Catalina Experimental Station, from October 2020 to July 2021. A completely randomized block-divided plot design with four replications was used. The factors under study were irrigation (with and without irrigation) and chemical fertilization (100 %, 50 % and 0% of the chemical fertilization recommendation), resulting in six treatments. Plant and ear height, nitrogen, phosphorus and potassium extraction, yield, water use efficiency and an economic analysis were evaluated. From the investigation it turned out that, when carrying out the water balance, there was an effective precipitation of 1 525 mm, evapotranspiration of the crop of 420 mm, for which it was necessary to apply irrigation of 209.37 mm to satisfy the water demand of the crop. The best response of water use efficiency was obtained with treatment 1 (with irrigation + 100% chemical fertilization) with 1.78 kg m-3. The highest values of nutrient extraction for nitrogen, phosphorus and potassium were obtained with the application of irrigation and 100 % of the recommended chemical fertilization with 148.81, 12.22 and 198.66 kg ha-1, respectively. The highest yield of 4.33 t ha-1 was obtained with the application of irrigation and 100% of the recommended chemical fertilization (76 kg ha-1 of nitrogen, 40 kg ha-1 of phosphorus and 22 kg ha-1 of potassium).